The Influence Of Relating, Experiencing, Applying, Cooperating And Transfering Learning Models Toward Chemistry Learning Outcomes - Wainda Sardika Dewi; Mukhtar Harris; Jackson Siahaan (Chemistry Education Program, the University of Mataram, 2018)
The purpose of this study was to investigate the effect of Relating, Experiencing, Applying, Cooperating And Transfering REACT model on chemistry learning outcomes of the eleventh grade students at the senior high schools in West Lombok Indonesia. The research type is quasi-experimental design with posttest only control group design. The population in this study were all the eleventh grade students and 80 students were taken as samples. They were determined through saturated sampling techniques. The reserach hypothesis testing was carried by the t-test. It was found that tcount 3.10 is higher that ttable (1.68) at a significant level of 5%. This result indicate that the application of the REACT learning model provides a better influence than conventional learning models on chemistry learning outcomes.